2013
DOI: 10.3390/ijerph10116027
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Infantile Mineral Imbalances in Autism Spectrum Disorders (ASDs)

Abstract: The interactions between genes and the environment are now regarded as the most probable explanation for autism. In this review, we summarize the results of a metallomics study in which scalp hair concentrations of 26 trace elements were examined for 1,967 autistic children (1,553 males and 414 females aged 0–15 years-old), and discuss recent advances in our understanding of epigenetic roles of infantile mineral imbalances in the pathogenesis of autism. In the 1,967 subjects, 584 (29.7%) and 347 (17.6%) were f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
59
0
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 75 publications
(64 citation statements)
references
References 79 publications
3
59
0
2
Order By: Relevance
“…Other studies have reported higher levels of aluminum in the hair [45,46,47] and urine [48] of children with ASD compared to children without ASD. Although it appears that our results contrast with results from other studies, the difference could be due to the differences in methods of assessment of aluminum concentrations; we determined the concentration of aluminum in blood while these other studies assessed aluminum concentrations in hair and urine.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Other studies have reported higher levels of aluminum in the hair [45,46,47] and urine [48] of children with ASD compared to children without ASD. Although it appears that our results contrast with results from other studies, the difference could be due to the differences in methods of assessment of aluminum concentrations; we determined the concentration of aluminum in blood while these other studies assessed aluminum concentrations in hair and urine.…”
Section: Discussionmentioning
confidence: 99%
“…Higher levels of aluminum were observed in the hair [45,46,47] and urine [48] of children with ASD, compared to children without ASD. One study from Egypt additionally found that the level of aluminum in children’s hair was positively correlated with the use of aluminum pans in the home [45].…”
Section: Introductionmentioning
confidence: 99%
“…In humans, Zn deficiency has additionally been associated with several neuropsychiatric diseases such as depression and autism2728293031. However, the pathophysiological correlations between Zn, Cu and ASD or PMDS are, especially on a molecular level, currently not well understood.…”
mentioning
confidence: 99%
“…In particular, the highest body burden (12.1 %) was observed in the infants aged 0-3 years, as already observed for lead, suggesting the existence of a critical period during neurodevelopment in which mineral imbalances of environmental toxic metals may induce epigenetic alterations and neurodevelopmental disorders Yasuda and Tsutsui 2013). Previously, the same authors had reported that not only Cd highest burden level was present in infants aged 0-3 years old but the metal mainly accumulated in females (Yasuda et al 2012).…”
Section: Association With Asds: Evidencementioning
confidence: 74%